2023
DOI: 10.3390/agronomy13102467
|View full text |Cite
|
Sign up to set email alerts
|

Crop Mapping and Spatio–Temporal Analysis in Valley Areas Using Object-Oriented Machine Learning Methods Combined with Feature Optimization

Xiaoli Fu,
Wenzuo Zhou,
Xinyao Zhou
et al.

Abstract: Timely and accurate acquisition of crop planting areas and spatial distribution are deemed essential for grasping food configurations and guiding agricultural production. Despite the increasing research on crop mapping and changes with the development of remote sensing technology, most studies have focused on large-scale regions, with limited research being conducted in fragmented and ecologically vulnerable valley areas. To this end, this study utilized Landsat ETM+/OLI images as the data source to extract ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Comparing our results with existing studies, Wang et al [46] achieved the highest OA of 77.12% by classifying large-scale regional crop types by combining four machine learning models and two deep learning models with time-series satellite data. Fu et al [28] constructed features based on multiscale segmentation and extracted crop information for the river valley area based on Landsat imagery. The OA was 86.97% and the kappa coefficient was 0.82.…”
Section: Discussion and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing our results with existing studies, Wang et al [46] achieved the highest OA of 77.12% by classifying large-scale regional crop types by combining four machine learning models and two deep learning models with time-series satellite data. Fu et al [28] constructed features based on multiscale segmentation and extracted crop information for the river valley area based on Landsat imagery. The OA was 86.97% and the kappa coefficient was 0.82.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Zhang et al [27] constructed a feature selection method based on the optimal extraction cycle of features based on Sentinel-2 remote sensing images, which significantly improved the recognition accuracy of mountain rice, with the best overall classification accuracy and kappa coefficient of 86% and 0.81, respectively. Fu et al [28] demonstrated that the Random Forest Recursive Feature Elimination (RF_RFE) algorithm can provide more useful features and improve the crop identification accuracy after feature selection by 1.43% to 2.19%, 0.60% to 1.41%, and 1.99% to 2.18% in 2002, 2014, and 2022, respectively, compared to crop identification without feature optimization. Jin et al [3] used Decision Trees to construct the optimal feature space in order to achieve fine crop classification and used an object-oriented Random Forest classification algorithm to classify the multi-feature space, and the final overall accuracy and kappa coefficient were 90.18% and 0.877, which were greater than for the pixel-level and single-feature classification accuracies.…”
Section: Introductionmentioning
confidence: 99%